2016
DOI: 10.7287/peerj.preprints.2346
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexual reproduction in the Caribbean coral genus Isophyllia (Scleractinia: Mussidae) in Puerto Rico

Abstract: rigida and refute the previous description for I. sinuosa.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Our observation that coral spat from the Family Lobophyllidae were exclusively found after six months of undisturbed artificial substrate availability substantiates the notion that there is a seasonal influence to the gametogenic cycle in this family. For example, Soto and Weil (2016) found that oogenesis for the species Isophyllia sinuosa and Isophyllia rigida correlated with warm local sea surface temperatures. Our study, reports the presence of spats belonging to the Family Lobophyllidae only in December 2014 which is after the major coral spawning period for Fiji and throughout warm temperate seasonality.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that coral spat from the Family Lobophyllidae were exclusively found after six months of undisturbed artificial substrate availability substantiates the notion that there is a seasonal influence to the gametogenic cycle in this family. For example, Soto and Weil (2016) found that oogenesis for the species Isophyllia sinuosa and Isophyllia rigida correlated with warm local sea surface temperatures. Our study, reports the presence of spats belonging to the Family Lobophyllidae only in December 2014 which is after the major coral spawning period for Fiji and throughout warm temperate seasonality.…”
Section: Discussionmentioning
confidence: 99%